2020
DOI: 10.1590/1516-3180.2019.0539.r1.05032020
|View full text |Cite
|
Sign up to set email alerts
|

Suicide mortality in the city of São Paulo: epidemiological characteristics and their social factors in a temporal trend between 2000 and 2017. Retrospective study

Abstract: BACKGROUND: Suicide is one of the leading causes of death worldwide, accounting for one million deaths annually. Greater understanding of the causal risk factors is needed, especially in large urban centers. OBJECTIVE: To ascertain the epidemiological profile and temporal trend of suicides over two decades and correlate prevalence with social indicators. DESIGN AND SETTING: Descriptive population-based longitudinal retrospective study conducted in the city of São Paulo, Brazil. METHODS: A temporal trend series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
4
0
2
Order By: Relevance
“…Ainda, no tocante à manipulação do corpo da vítima, além do SAMU, a família possuiu significativa participação no relato dos peritos, principalmente em casos de suicídio, na tentativa de socorro ao parente. Estudos realizados no Brasil, apontaram o ambiente domiciliar como o local de maior ocorrência dos casos de suicídio, e o enforcamento se destaca como o método mais prevalente (12)(13) . Esses achados corroboram o cenário mundial conforme observado em revisão de escopo realizada por pesquisadores da Austrália, na qual 36 artigos foram analisados e, destes, 17 que apontavam o local de ocorrência do enforcamento, mostraram o domicílio como o de maior utilização da força (14) .…”
Section: Discussionunclassified
“…Ainda, no tocante à manipulação do corpo da vítima, além do SAMU, a família possuiu significativa participação no relato dos peritos, principalmente em casos de suicídio, na tentativa de socorro ao parente. Estudos realizados no Brasil, apontaram o ambiente domiciliar como o local de maior ocorrência dos casos de suicídio, e o enforcamento se destaca como o método mais prevalente (12)(13) . Esses achados corroboram o cenário mundial conforme observado em revisão de escopo realizada por pesquisadores da Austrália, na qual 36 artigos foram analisados e, destes, 17 que apontavam o local de ocorrência do enforcamento, mostraram o domicílio como o de maior utilização da força (14) .…”
Section: Discussionunclassified
“…The suicide rate in Brazil varied from 4.82 to 6.9 per 100,000 habitants along with different studies from different years (Martini et al,. 2019;Colombo-Souza et al,. 2020;Dantas et al,.…”
Section: Suicide Rate In Brazilmentioning
confidence: 99%
“…2018). A study in the city of São Paulo, the most populous city in the country located in the Southeast region, found that suicide rates increased from 4.6/100,000 inhabitants in 2000 to 4.9/100,000 in 2017 (Colombo-Souza et al,. 2020).…”
Section: Suicide Rate In Brazilmentioning
confidence: 99%
See 1 more Smart Citation
“…Introdução O suicídio de idosos, pessoas com 60 anos ou mais, é considerado pela Organização Mundial da Saúde como um dos mais graves problemas de saúde pública, pois o risco aumenta com a idade [1][2][3][4][5][6][7][8][9] e essa é a população em maior crescimento [7].…”
unclassified